Distal Renal Tubular Acidosis Presenting as Recurrent Paralytic Crises A Case Report - Rupali Malik; Nabadwip Pathak (Medicine Science, 2015)
Renal tubular acidosis (RTA) is a syndrome resulting from tubular dysfunction leading to deranged acid-base balance. One of the subtypes, distal RTA manifests as renal parenchymal stone disease with nephrocalcinosis, evidence of vitamin D deficiency and growth faltering in children with ultimate short stature in adulthood. The physician should be familiar with the condition, in order to expedite correct management and ameliorate the complications. We hereby report a case of distal renal tubular acidosis (dRTA), who presented with recurrent hypokalemic paralysis and osteopenia but, unusually, without any nephrocalcinosis. [Med-Science 2015; 4(4.000): 2933-7]